The 2015 Gorkha Nepal Earthquake: Insights from Earthquake Damage Survey - Goda, Katsuichiro; Kiyota, Takashi; Pokhrel, Rama Mohan; Chiaro, Gabriele; Katagiri, Toshihiko; Sharma, Keshab; Wilkinson, Sean (Frontiers in Built Environment, 2015)
The 2015 Gorkha Nepal earthquake caused tremendous damage and loss. To gain valuable lessons from this tragic event, an earthquake damage investigation team was dispatched to Nepal from 1 May 2015 to 7 May 2015. A unique aspect of the earthquake damage investigation is that first-hand earthquake damage data were obtained 6 to 11 days after the mainshock. To gain deeper understanding of the observed earthquake damage in Nepal, the paper reviews the seismotectonic setting and regional seismicity in Nepal and analyzes available aftershock data and ground motion data. The earthquake damage observations indicate that the majority of the damaged buildings were stone/brick masonry structures with no seismic detailing, whereas the most of RC buildings were undamaged. This indicates that adequate structural design is the key to reduce the earthquake risk in Nepal. To share the gathered damage data widely, the collected damage data (geo-tagged photos and observation comments) are organized using Google Earth and the kmz file is made publicly available.